Perbandingan Performa Routing Protocol antara Mixed Routing Protocol dengan Single Routing Protocol pada Aplikasi VoIP Menggunakan Riverbed Modeler Academic Edition 17.5 - Dewa Nyoman Suartama Ariawan; Gede Saindra Santyadiputra; I Ketut Resika Arthana (Jurnal Ilmu Komputer, 2021)
VoIP is a communication technology device that is used by companies and homes to communicate. So far, there are several shortcomings of VoIP that may impact the real conditions in the field, so it is necessary to have a combination of routing protocols that can cover the shortcomings of both the VoIP application and the routing protocol. This study aims to conduct a comparative study of the performance of mixed routing protocols with single routing and to test IPv4 and IPv6 using semi-mesh topology and mesh wireless network topology in VoIP applications. This study uses the OPNET Riverbed Modeler Academic Edition 17.5 simulation method with a design and analysis model that includes the stages of create network model,modeling, application, profile and failure / recovery configuration, choose statistics, run simulation, view and analyze the results. The results showed that the combination of EIGRP-IGRP-ISIS-OSPF-RIPv2 and RIPv2-ISIS-EIGRP provided good research results and covered the weaknesses of RIPv2, IS-IS and EIGRP compared to single routing protocols, both in semi-mesh and wireless mesh topologies. network.mixed routing protocol. The addition of the variance of the comparison between IPv4 and IPv6 based on a single routing protocol also shows significant results, where both IPv4 and IPv6 in the semi-mesh topology and the mesh wireless network are in a range partly in good and very good ranges with the rest being sufficient, bad and very bad.